2003
DOI: 10.1046/j.1365-2982.2003.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of position on oesophageal function: studies using combined manometry and multichannel intraluminal impedance

Abstract: Multichannel intraluminal impedance (MII) allows assessment of intraoesophageal bolus transit. In the supine position, bolus transit is produced almost exclusively by peristaltic contractions; in the upright position, gravity also contributes to bolus transit. MII and peristaltic pressures were measured in four positions (0, 30, 60 and 90 degrees ) using ten swallows (5 cc each) of both water and viscous liquid with body position determined by random choice. Tracings were analysed for total bolus transit time:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
(21 reference statements)
6
31
0
1
Order By: Relevance
“…Moving from the supine to the upright position increased oesophageal velocity and decreased contractile pressure, changes that likely reflect a reduction in workload required for bolus transport in the upright position. [24][25][26][27] There was a further increase in oesophageal velocity and decrease in contractile pressure after the meal. This may also reflect the reduced resistance to bolus transport following the fall in LOS pressure and length after a meal.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moving from the supine to the upright position increased oesophageal velocity and decreased contractile pressure, changes that likely reflect a reduction in workload required for bolus transport in the upright position. [24][25][26][27] There was a further increase in oesophageal velocity and decrease in contractile pressure after the meal. This may also reflect the reduced resistance to bolus transport following the fall in LOS pressure and length after a meal.…”
Section: Discussionmentioning
confidence: 94%
“…Results from the mixed model ANOVA revealed that tegaserod had no effect on median LOS pressure compared with placebo [23 (18-29) vs. 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) …”
Section: Effect Of Tegaserod On Oesophageal Peristalsis and Sphinctermentioning
confidence: 99%
“…Bolus entry was defined as ≥ 50% decrease in impedance with respect to baseline. [12][13][14] Bolus clearance was defined as sustained (> 5 seconds) ≥ 50% increase in impedance from the original baseline impedance. 15 Complete bolus clearance was defined as bolus entry followed by bolus clearance at all impedance recording sites, and incomplete bolus clearance was defined as bolus entry followed by failure of bolus clearance at any of the impedance recording sites.…”
Section: Discussionmentioning
confidence: 99%
“…In the isobaric 30-mmHg contour, the median (interquartile range) length of the break of incomplete bolus clearance was 13.5 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) cm and that of complete clearance was 3 (1-6) cm (P < 0.001).…”
Section: Isobaric Contour and Breaks Associated With Incomplete And Cmentioning
confidence: 98%
“…En cuanto al método utilizado para realizar el estudio radiológico, la mayor proporción del tiempo el paciente se encuentra en decúbito supino, lo cual ha sido demostrado aumenta los episodios de RGE en exámenes de monitoreo de pH en 24 horas (23)(24) . El volumen de bario utilizado no ha sido estandarizado, pero la recomendación es utilizar una cantidad suficiente como para obtener una adecuada oferta a la unión gastroesofágica, evaluada bajo visión fluoroscópica.…”
Section: Discussionunclassified